Experimental Study of Evaporation Flux, Salt Precipitation, and Surface Temperature on Homogeneous and Heterogeneous Porous Media - Xinhu Li; Min Guo (Advances in Civil Engineering)
Salt precipitation in porous media is widespread, which has garnered great research attention. However, the mechanisms governing the salt precipitation, water flux, and surface temperature changes in homogeneous and heterogeneous porous media remain unclear. This study investigated the dynamics of salt precipitation, evaporative loss, and surface temperature in homogeneous fine sand (0.1–0.25 mm), coarse sand (1-2 mm), and a heterogeneous column with fine and coarse sand. All sand columns were initially saturated with NaCl solution. The experimental results showed that the salt was precipitated as efflorescence above the surface of the fine sand, whereas it was mainly precipitated as subflorescence below the surface of the coarse sand, causing the unconsolidated sand to form a strong stone-like mass. The evaporated loss was significantly higher in heterogeneous than in homogeneous sand, but this difference in evaporation was insignificant in the stage where vapor diffuses through the precipitated salt to the external air. The salt crust formed not only decreased the surface temperature due to increased albedo by salt precipitation, but also resulted in a more discrete temperature distribution in the porous media. Our research results can promote further understanding of salt precipitation and evaporation in porous media.